2010
DOI: 10.4310/sdg.2010.v15.n1.a2
|View full text |Cite
|
Sign up to set email alerts
|

Subgroups of depth three

Abstract: A subalgebra pair of semisimple complex algebras B ⊆ A with inclusion matrix M is depth two iff MM t M ≤ nM for some positive integer n and all corresponding entries. If A and B are the group algebras of finite group-subgroup pair H < G, the induction-restriction table equals M and S = MM t satisfies S 2 ≤ nS iff the subgroup H is depth three in G; similarly depth n > 3 by successive right multiplications of this inequality with alternately M and M t . We show that a Frobenius complement in a Frobenius group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…For example, for the permutation groups Σ n < Σ n+1 and their corresponding group algebras B ⊆ A over any commutative ring K, one has depth d(B, A) = 2n − 1 [6,4]. Depths of subgroups in P GL(2, q), twisted group algebras and Young subgroups of Σ n are computed in [10,9,11].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for the permutation groups Σ n < Σ n+1 and their corresponding group algebras B ⊆ A over any commutative ring K, one has depth d(B, A) = 2n − 1 [6,4]. Depths of subgroups in P GL(2, q), twisted group algebras and Young subgroups of Σ n are computed in [10,9,11].…”
Section: 2mentioning
confidence: 99%
“…(We have seen in Section 1 that ⇒ is more generally true.) It is known that a semisimple complex algebra-subalgebra pair form a split, separable Frobenius algebra extension [3,6,17]. From [35,37] and group theory, the following is a common setup.…”
Section: Uniquely Separable Frobenius Extensionsmentioning
confidence: 99%
“…Let G be a finite group, and Cl(G) denote the set of conjugacy classes of G. For group algebras, we recall where B has minimum polynomial (X − 1)(X − 3) and C has minimal polynomial X(X − 1)(X − 3). The depth is computed to be d 0 (S 2 , S 3 ) = 3 in [10] (and d 0 (S n−1 , S n ) = 2n − 1 in [11], d h (S n−1 , S n ) = 2n + 1 [35]). Proof.…”
Section: Minimal Polynomials Of Q In A(r) and A(h)mentioning
confidence: 99%
“…Although the depth two subgroups are precisely the normal subgroups [8], a similar description is not yet known for any higher depth. For example, in [4] a sufficient condition for depth three was given but it is not yet known if that condition is necessary. More precisely if H ⊂ G is an extension of finite groups, it was shown that H is a depth three subgroup of G provided that there is x ∈ G such that H…”
Section: Introductionmentioning
confidence: 99%